Sources of Finance and Performance of Microenterprises in Haryana - Mor, Nishant; Mor, Surender (International Journal of Psychosocial Rehabilitation, 2020)
The impact of sources of funding on the performance of microenterprises has been examined on 500 Microentrepreneurs across the Haryana state of India. Post hoc test and Welch test has been employed to find a significant difference among various sources of finance and their possible impacts on the sale proceeds of the selected micro business. The findings indicate that sources of finance are crucial determinants for the growth performance of the microenterprises. The micro-businesses availing advances from NBFCs have reported significantly higher sale proceeds in their respective enterprises as compared to other sources like personal savings, bank loans, family wealth, and the loan from family & friends. The study infers that there is a dire need to develop the sources of venture funding for the microenterprises as it is directly related to their sale proceeds in Haryana. The funding pattern of NBFCs may also need to be taken care for augmenting and meeting the financial need of the need microenterprises.